Multi-Disciplinary Approaches to Learning and Teaching in Kenya: Use of Video Games in Education - Aseey, Anne Achieng (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Education is one sector that tries to be consistent despite facing several changes. Vari- ous factors and emerging trends have affected the sector both positively and negatively. The scope of the digital divide is more pronounced in the developing countries and the COVID-19 pandemic exacerbated the technological struggles in Africa more than before. Technology is an enabler in education but not in all contexts because it also causes other challenges that increase the vulnerability of learners and educators in diverse circumstances. The proliferation of digital devices, especially mobile and smart devices, has brought in new changes and innovative ideas that have impacted the sectors input, output, and outcome. Leaners have demonstrated various degrees of adoption and absorption of new devices, and simultaneously educators have integrated and adapted to new pedagogies that resonate with the situation. As a continent, Africa has experienced an emerging trend with digital and non-digital devices interconnected for educational purposes on demand whenever needed. In developing countries like Kenya, more innovative ways of learning have been harnessed for learning and teach- ing purposes .With the penetration of the World Wide Web, the internet of things, availability of electronic devices, and improvement in information communication and technology infrastructure. Video games, which can be played on many platforms and electronic devices, can easily be leveraged for teaching and learning purposes. This study was conducted among learners and educators in an urban setting in Nairobi County, Kenya. The study investigated the potential of video games in education as used by leaners and teachers. The findings indicated that most leaners targeted had personal mobile devices. This gave them easy access to video games, which led to the popularity of these games. The findings also indicated that the leaners were not allowed to use digital devices like mobile phones in the classroom at school but had limited access to video games through desktops and laptops available in their institutions. The findings also showed that the majority of teachers were not keen on using video games for teaching and learning purposes, and this scenario presented a disparity in and a barrier to using multi-disciplinary approaches and integrating technology in teaching and learning. The study recommended that, with more electronic devices available for leaners and other education stakeholders, it is necessary to harness video games for learning and teaching purposes to allow for innovation, discovery, critical thinking, and experiential learning among learners.